Patient and clinician perspectives of an eHealth intervention for supporting cancer treatment in the UK: mixed methods evaluation of the eRAPID randomised controlled trial - Galina Velikova; Lorraine Warrington; Kate Absolom; Patricia Holch; Andrea Gibson; Jenny Hewison; Claire Hulme; Julia Brown; Bryony Dawkins; Marie Holmes; Rosemary Peacock; Zoe Rogers; et al. (BMJ Open)
Objectives During 2015–2018, a randomised controlled trial (RCT) evaluated eRAPID, an eHealth intervention designed to capture patient-reported symptoms online during cancer treatment. eRAPID provides patients with advice on when to self-manage or seek medical support. Clinicians accessed symptom reports within electronic patient records. 508 participants starting systemic cancer treatment were recruited and followed for 18 weeks. The intervention group (n=256) was asked to access eRAPID and complete weekly online symptom reports. Clinicians received training on accessing and interpreting symptom reports. Overall, eRAPID had a positive impact on patients’ symptoms, quality of life and self-efficacy, particularly early in treatment and for patients with early-stage disease. Using mixed methods, we aimed to gather insight from patients and clinicians on how eRAPID worked to facilitate the interpretation of RCT findings.Methods Following a concurrent triangulation design, patient experiences of eRAPID were gathered via end-of-study interviews (n=45) and questionnaires (n=186). Clinician experiences were obtained by end-of-study interviews (n=18) and completion, throughout the trial, of feedback questionnaires (n=787 from n=55 clinicians). Framework analysis was applied to examine qualitative data and close-ended questions were descriptively summarised. Findings were mapped against results from the RCT.Setting Medical oncology services, UK cancer centre.Results Patient feedback indicated eRAPID was easy to use. Adherence to weekly reporting was influenced by health status, reminders, perceived value and clinical use. Patient-reported benefits of eRAPID included an enhanced connection with the hospital, provision of practical advice and personal monitoring, which provided reassurance and empowerment. Clinicians were positive about the potential for online symptom monitoring but had mixed levels of direct experience with using eRAPID during the trial. Patients echoed this and recommended more explicit clinician use of symptom data.Conclusions The mixed-method approach to capturing patient and clinician opinions provided valuable insight into the eRAPID intervention and complementary information on how the intervention was received and functioned.